Occurrences of pharmaceuticals and personal care products in the drinking water of Taiwan and their removal in conventional water treatment processes. (October 2020) - Pai, Chih-Wei; Leong, Dexter; Chen, Chia-Yang; Wang, Gen-Shuh
Abstract: Pharmaceuticals and personal care products (PPCPs) has been of concerns for their potential threats to ecosystems and human's health for decades. PPCPs have been detected in water environments worldwide and have been identified in water sources and finished water. To elucidate the potential exposure of PPCPs in drinking water, this study assessed the occurrences and treatment efficiencies of PPCPs in the drinking water of Taiwan. Raw and finished water samples collected from five main drinking water treatment plants (DWTPs) in February, June, and November 2018 were analyzed. Furthermore, laboratory-scale water treatment processes were conducted to evaluate the treatment efficiencies of these chemicals. Most of the water samples from the DWTPs had a low concentration (<30 ng/L) of PPCPs. Only samples from a DWTP was observed to have higher concentration of ibuprofen (55.6 ng/L), benzophenone (92.5 ng/L), caffeine (390.5 ng/L), and diethyltoluamide (DEET) (434.9 ng/L) in raw water than others. The results of laboratory simulations indicated that the pre-chlorination process was the key step responsible for the removal of PPCPs in conventional water treatment processes, which can remove most of the hormone treatment products, parabens, oxybenzone, and acetaminophen in water sources. However, the filtration process with anthracite as a medium could remove some of the parabens (approximately 11.9%–41.2%), hormones (approximately 18.2%–44.8%), suntan lotions (37.5%–68.8%), and naproxen (30.1%) from Milli-Q water. The removal efficiencies of the aforementioned chemicals were marginally lower in raw water. However, analgesics, caffeine, and DEET cannot be removed effectively through conventional drinking water treatment. Graphical abstract: Image 1 Highlights: PPCP removals in conventional water treatment processes were assessed. PPCPs were spiked in different water matrices to compare the matrix effects. Removals after chlorination depend on structures of PPCPs. Adsorption plays an important role for PPCP removals in rapid filtration process. UV/chlorine process improve the overall removal of PPCPs.